Detection of Material Fatigue in Polyvinyl Chloride (PVC) for Bouncy Castle Application - Stephen, Abayomi; Croman, Darren; Holborn, Mark (Open Science Journal, 2025)
The creation and design of a conceptual electronic and electromechanical equipment setup for material fatigue detection in Bouncy Castles made of polyvinyl chloride (PVC) material is what we suggest in this work. By utilising this cutting-edge equipment setup, which includes what we call a Camera Columnar System (CCS) that operates on the Fourier Transform Infrared Spectroscopy (FTIR) principle mounted on an Electro-Mechanical Conveyor System (EMCS), we can apply targeted material analysis while kids are actively playing on the Bouncy Castles. To identify any anomaly or variation, the PVC's FTIR map distributed band spectrum displayed on the CCS/EMCS are compared with FTIR spectrum of pure PVC stored in the equipment’s memory. From the results obtained by this comparison, if an anomaly or variation is found, this we suggest could be a sign of material fatigue brought on over time by stress, strain, photodegradation, and environmental temperature fluctuations. We believe that this CCS/EMCS proposed concept will aid in reducing accidents and fatality.